Entropic-energy model of fatigue defects development - Делас, Николай Иванович; Касьянов, Владимир Александрович (Eastern-European Journal of Enterprise Technologies, 2012)
The dependence is deduced on the basis of the maximum entropy method, to distribute the number of fatigue microcracks according to the category of absorbed energy. The ratio obtained is non-Gaussian and is called “The ultimately hyperbolic distribution law”, which becomes asymptotically hyperbolic with the growth of argument. That plot allows the microcracks to “distribute” the absorbed energy in the most reasonable way. The energy balance for the microcrack’s absorbed energy is made out, proceeding from the supposition that the increase of its area is in proportion to the gap energy of intercrystalline links, and the dissipation energy in the plasticity area is in proportion to the size of its borders. This gave an opportunity to obtain the ratios for the growth indicators of microcrack’s area. These results and taking account of microcracks’ distribution according to the categories of absorbed energy, help to get the evaluation formula for the fatigue plot.